Implementasi Hukum Terhadap Pembatalan Lelang Eksekusi Hak Tanggungan - Rapiq, Muhammad; Hapsari, Recca Ayu (Universitas Pancasakti Tegal, 2021)
The purpose of this research is to assess how the implementation of the cancellation of the auction of the execution of dependent rights on a piece of land in Sukadamai Village of Natar District of South Lampung Regency based on Decision Number: 39/ Pdt.Bth / 2019 / PN. Kla? and what are the factors inhibiting the implementation of the cancellation of the auction of the execution of dependent rights on a piece of land in Sukadamai Village of Natar District of South Lampung Regency based on Decision Number: 39/Pdt.Bth/2019/Pn.Kla.? Research methods use normative and empirical juridical approaches. The types of data used are secondary data and primary data. Data collection through library research and field research. The data analysis used is qualitative juridical. The results of the study showed that the auction can be canceled if the auction process is not in accordance with the correct procedure, this can only be canceled by a court ruling with permanent legal force (provisional). The provisions are in accordance with the sound in Article 24 of the Regulation of the Minister of Finance Number 106 / PMK.06 / 2013. The legal consequences arising against the auction object is the return of the auction object to its original status, namely as a guarantee object held by the holder of the Dependent Rights certificate. The right of the winner of the auction to the auction item that has been won by him will be lost and the item will return to its original status to the auction seller.